Laser impact welding: Design of apparatus and parametric optimization. (August 2015) - Wang, Huimin; Taber, Geoff; Liu, Dejian; Hansen, Steve; Chowdhury, Enam; Terry, Scott; Lippold, John C.; Daehn, Glenn S.
Abstract: Laser impact welding (LIW) is a solid-state, collision-based welding process. Applications may include joining of dissimilar metals for small-scale parts such as those used in medical devices and microelectronics. The current work focuses on the development of the LIW process for industrial applications with commercial available materials. In this technique, a pulse of high power laser light was converted to kinetic energy through the ablation of a coating on the flyer surface. A transparent confining window directed the force of the expanding gas to launch a flyer toward a target plate. A suitable laser system with diagnostics is described. An experimental study of parameters affecting ablation pressure was conducted via an analysis of flyer deformation and launch velocity. A laminated multi-launch package with a CNC-based motion control welding apparatus was constructed with informed selection of components to optimize conversion efficiency. This joining system is used to demonstrate the LIW joining of aluminum and titanium.